Integrating Archaeological Tourism And Ecotourism: Experiences From Egypt And India - Aruna Rao , Shalini Saksena (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Tourism, especially sustainable tourism is considered to be the foremost engine of the post-industrial growth phase in both the developed and developing countries. In countries that possess rich natural and cultural heritage, ecotourism along with archaeological tourism has enormous potential and implications for sustainable development. This paper highlights the different concepts of tourism tied together with a common underlying philosophy of promoting travel with a purpose. Further, developments in view of promoting ecotourism along with archaeotourism in Egypt and India are examined by undertaking a case study of an Oasis in Egypt and a National park in India, and carrying out a SWOT analysis to summarise the experiences and suggest the way forward.